A Cross Sectional Study on the Risk Factors of Illicit Drug use Among the University Students - Saeed Akbar Tariq, Muhammad Afzal, Rashid Mahmood Khan, Muaaz Tariq, Atif Maqsood, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The aim of this study was to assess the prevalence of illicit drug use among university students of private and public universities. And also, to assess risk factors of illicit drug use. Methods: This study was conducted at DHQ Hospital Faisalabad and the duration of this study was from November 2020 to April 2022. This was a cross sectional study design, in which data was collected from 600 students of public and private sector universities. The sample had an equal gender proportion i.e 300 males and 300 females. Data was collected through questionnaires. The data was then analyzed for the prevalence of illicit drug use among university students and also the associating risk factors of illicit drug use. Chi square test was performed to find out the association of illicit drug use to various factors such as age, living status, availability, source of drug, frequency of intake etc. Result: According to data analysis 17.3% students of government colleges were using more than one drug while 82.6% were using single drugs. 26.3% students of private colleges were using more than one drug while 73.6% were using single drug. 80% of public sector had abused prescribed drugs. 73.6% of private sector had abused prescribed drugs. 19.2% public sector students knew multiple drug suppliers. 46.9% students revealed that the drug was available within the university premises. Practical Implication: Our finding of the increased risk of illicit drug use among the university students has added an important information to the literature in this research area. The aim of this study was to investigate the risk factors of illicit drug use among the public and private university students of Punjab. We also tried to learn the reason for the usage of these drugs and also whether these are any factors associated with use of these illicit drug. Conclusion: Illicit drug use is more prevalent in boarders as compared to day scholars. A chunk of the students revealed that the drugs most commonly used are cheap. Drugs are more easily available in public sector universities as compared to private ones. There has been a gradual increase in the frequency of drug intake per day in addicts. Illicit drugs had an overall negative effect on the academics of students. A good proportion of the sample believes that parental care plays a key role in preventing their child from indulging into any type of illicit drug use. Keywords: Drugs, Risk Factors, Addicts, Maladaptive, Psychologically, Neurotransmitters